Independent films and streaming platforms: access difficulties for peruvian filmmakers - Mateo, Jazmin (2022)
The pandemic caused by COVID-19 has created an uncertain scenario for independent films, forcing them to explore other exhibition opportunities and having streaming as the protagonist. In this context, identifying the access gaps that Peruvian cinema have for entering the international market in a digital environment is a topic of current interest. This article aims to identify the difficulties encountered by Peruvian independent films in order to enter the main platforms (Netflix, HBO, Amazon Prime, among others). The methodology used is based on semi-structured interviews conducted to Peruvian filmmakers who have had the experience of having their films via streaming. In order to understand better the object of study, an in-depth interview was conducted to the General Management of Guarango Cine y Video, which is a production studio specialized in post-production, delivery and preparation of films for digital platform. For analyzing the results, there is a classification proposal of difficulties: technical, economical, production and socio-cultural. These four categories and their effect on film circulation are the central axis of this research. The most important findings of the research suggest that economic issues and the lack of knowledge or planning in terms of distribution possibilities are the main and transversal difficulties encountered by independent Peruvian filmmakers to exhibit on streaming platforms.